KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMK MATERI MATRIKS DITINJAU DARI GAYA KOGNITIF ADAPTASI DAN INOVASI - Aulia Diraswati Septyanggraeni; Masriyah Masriyah; Endah Budi Rahaju (IKIP Siliwangi, 2023)
In this research, the authors investigated difference in the mathematical problem-solving abilities of students at SMKN 1 Grati Pasuruan, in terms of the cognitive style of adaptation and innovation of class XI. Data collection was carried out by giving an Adaptation-Innovation in Workplace s (AI-W) questionnaire to determine students' cognitive styles and the Matrix Problem Solving Task (TPMM) to measure the mathematical problem solving abilities. Data collection is used to obtain relevant and accurate data. The methods used for data analysis techniques are questionnaires, tests, and interviews. In this study, students with an adaptive cognitive style were able to fulfill three of five indicators of solving mathematical problems, while subjects with an innovative cognitive style were able to fulfill four of them. The results of this research indicated that students in the innovation group performed better than the adaptation group. Overall, these results provide a more detail description of individual differences in the math problem-solving abilities of SMK students on the matrix.